2021
DOI: 10.1136/bmjresp-2021-000939
|View full text |Cite
|
Sign up to set email alerts
|

Performance of popular pulse oximeters compared with simultaneous arterial oxygen saturation or clinical-grade pulse oximetry: a cross-sectional validation study in intensive care patients

Abstract: ObjectivesTo evaluate the performance of direct-to-consumer pulse oximeters under clinical conditions, with arterial blood gas measurement (SaO2) as reference standard.DesignCross-sectional, validation study.SettingIntensive care.ParticipantsAdult patients requiring SaO2-monitoring.InterventionsThe studied oximeters are top-selling in Europe/USA (AFAC FS10D, AGPTEK FS10C, ANAPULSE ANP 100, Cocobear, Contec CMS50D1, HYLOGY MD-H37, Mommed YM101, PRCMISEMED F4PRO, PULOX PO-200 and Zacurate Pro Series 500 DL). Dir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Seven of the 15 studies (with 503 participants) were not included in meta-analysis (Supporting Information Table S6): [38,[41][42][43][44]53,54] six compared differences in mean bias between pigmentation levels, rather than reporting mean bias by levels of skin pigmentation. Where relevant and available we present data by device type in Supporting Information Table S6, there may be some variation in the amount of mean bias based on device used but data are too limited to draw further conclusions.…”
Section: Figure 2 Risk Of Bias Assessment Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven of the 15 studies (with 503 participants) were not included in meta-analysis (Supporting Information Table S6): [38,[41][42][43][44]53,54] six compared differences in mean bias between pigmentation levels, rather than reporting mean bias by levels of skin pigmentation. Where relevant and available we present data by device type in Supporting Information Table S6, there may be some variation in the amount of mean bias based on device used but data are too limited to draw further conclusions.…”
Section: Figure 2 Risk Of Bias Assessment Resultsmentioning
confidence: 99%
“…Using QUADAS-2, we considered 14/32 studies (43.75%) to be at unclear risk of bias for all four domains or high risk of bias for at least one domain, [34,38,44,47,48,53,54,[56][57][58][59][60][61]63] and the remaining 18 (56.25%) to be at low risk of bias for at least one of the four domains (Figure 2).…”
Section: Assessment Of Risk Of Bias and Applicabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing these recommendations is important in understanding the risk of measurement inaccuracy and providing the highest outcomes [ 26 ]. Nevertheless, a recent study revealed that a pulse oximetry device provided good accuracy in ruling out hypoxemia in comparison to saturation reading by arterial blood gas sample [ 27 ].…”
Section: Discussionmentioning
confidence: 99%